Observational evidence from patients diagnosed with chronic lymphocytic leukaemia (CLL) in Finland between 2005‐2015 show improved survival over time. (25th July 2019) - Lindström, Vesa; Hakkarainen, Katja M.; Mehtälä, Juha; Klement, Riho; Leval, Amy; Järvinen, Tiina M.
Abstract: Objectives: We aimed to describe treatment patterns of chronic lymphocytic leukaemia (CLL) patients in routine practice settings, compare overall survival and time‐to‐next‐treatment among patients treated in different time periods (2005‐2008, 2009‐2013, 2014‐2015), and explore associated factors. Methods: This retrospective cohort study included adult CLL patients from the Finnish Hematology Registry. Results: In total, 124 and 64 CLL patients received first‐ and second‐line treatments, respectively. The use of first‐ and second‐line treatments with bendamustine‐rituximab (BR) increased, while chlorambucil‐based treatments decreased over time. Patients treated in more recent years showed a trend towards longer first‐ and second‐line survival. A trend towards inferior overall survival was detected in first‐ and second‐line treatment with B/BR. First‐line time‐to‐next‐treatment was longer for patients treated in the later years towards 2015, while second‐line time‐to‐next‐treatment did not improve over time. Conclusions: This study identified that improved treatment outcomes over time were likely influenced by patient characteristics and treatments, but also through other factors unexplored in this study. Hence, further research on the factors influencing patients' survival over time is needed. In particular, research on using B/BR in clinical practice is warranted.